Clinical Experience Over 15 Years with the B-Lynch Compression Suture Technique in the Management of Postpartum Hemorrhage - Gilberto Nagahama; Henri Augusto Korkes; Nelson Sass (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To describe the clinical experience with the B-Lynch technique in the management of postpartum hemorrhage as well as the factors related to the indication of the technique and to present the success rates of the application of the B-Lynch technique. Methods Observational, retrospective, cross-sectional, and analytical study. Patient data was obtained through the study of medical records. The study population comprised of patients who underwent hemostatic suture using the B-Lynch technique, including 104 patients within the period from January 1, 2005, to December 31, 2019. Results Of the total of 104 patients, 82.7% did not present any complications. Blood transfusion and intensive care unit admission were the most prevalent complications, with 13.5% and 15.4%, respectively. Only 1% of the patients had puerperal and surgical site infections. The factors most related to the application of the technique were the presence of previous cesarean section (30.8%), use of oxytocin (16.3%), and pre-eclampsia (11.6%). Puerperal hysterectomy was performed in 4.8% of the patients due to failure of the method. Conclusion The clinical experience with the B-Lynch technique was satisfactory since it presented few complications, with excellent results in hemorrhagic control. Previous cesarean section, the use of oxytocin, and preeclampsia stood out as factors related to the indication of the application of the technique, and the success rate in controlling postpartum hemorrhage was 95.2%.